Labirintogoria : estados de reverberação no encontro com a arte - Velho, Ângela Teresinha Fontana de Souza Tambara (2021)
ABSTRACT: The purpose of this thesis is a reflection on the unfolding of what we experience in the encounter with contemporary art and the development of what we usually call experience, experience, affectation, event. I present and develop the notion of a state that we will here name labirintogoria, involving the capacity for knowledge /experience / learning according to the theory of the Stoics' incorporeals. It is not just about being affected, witnessing something overwhelming, suffering an experience or going through an experience or event, but a process of elaboration, its reverberations and its continuum.